Associations between depression, anxiety, stress, hopelessness, subjective well-being, coping styles and suicide in Chinese university students - Abu Talib, Mansor; Huen, Jenny; Yu, Peng Peng; Yuan, Lu; Wang, Dong Fang; Ping, Fan; Lester, David; Jia, Cun Xian; Lew, Bob (Public Library of Science, 2019)
Suicide is a major public health concern worldwide. This study aimed to predict the suicidal behavior of Chinese university students by studying psychological measures such as hopelessness, orientation to happiness, meaning in life, depression, anxiety, stress, and coping styles. In November 2016, a stratified-clustered-random sampling approach was utilized to select subjects from two large public medical-related universities in Shandong province, China. This sample consisted of 2,074 undergraduate students (706 males, 1,368 females; mean age = 19.79±1.39 years). The students' major risk factors for suicide were depression, anxiety, stress, and hopelessness, and the students' minor risk factors included orientation to happiness and coping styles (including self-distraction, self-blame and substance use). Notably, the presence of meaning in life had a positive effect on preventing suicide and acted as a protective factor, which suggests that it is important to identify risk factors as well as protective factors relevant to the target population group in order to increase the effectiveness of counseling and suicide prevention programs.